Interfaces acessíveis para usuários que são cegos : um método de representação tátil e sonora da informação em bioinformática estrutural - Côrtes, Vanessa Stangherlin Machado Paixão (2019)
Structural bioinformatics uses computational techniques to study macromolecules that have structures, such as DNA and proteins. They have structural details that are difficult to understand, manipulate and visualize because they require abstractions based on a three-dimensional (3D) interface. In this sense, blind students face difficulties in understanding them. To minimize this problem and to help the learning of these contents, tactile concrete materials are used. However, the same is not true in computational environments, as the molecule visualization and manipulation tools are not accessible. This thesis aims to devise a method to represent visual and 3D information of structural bioinformatics that integrates haptic and sound elements so that they can be accessed and manipulated by blind people. Based on the user-centered design process, the context analysis, specification and design of interface solutions and method validation steps were performed from the perspective of blind and / or expert users. We conducted nine studies, which included a case study, a data collection with 29 teachers, a systematic literature review, the creation of concrete material, automated and manual accessibility testing, and blind user training. The analysis of the results allowed the composition of a set of 77 software requirements and 26 best practice recommendations for image description and construction of concrete materials, which were used to design a tangible interface called DeMOLidor and a web tool for sound navigation. 3D protein structures, the WalkingMOL. We held a workshop with 15 visually impaired users to validate the solutions developed. The results of the workshop showed that concrete materials, DeMOLidor and WalkingMOL are suitable for users' needs and favor the interaction of blind people with 3D visual and structural bioinformatics information, validating the requirements and best practice recommendations with which were built.